Judge Al Villa Swears In New Attorney Cristobal Perez - Watkins, Howard::::::::: (1983)
Janice Pearson, Howard Watkins, Doris Burnes, Alice Gutierrez, Virginia Salmeron, Ruben Lucero, Betsy Temple, Judge Al Villa, Cristobal Perez, Charles Kahill, Aggie Rose, Elaine Harris in courtroom